Caixing Lun in Liu Shao’s Renwu Zhi during the Wei-Jin period - Zhang, Na; Peter Gan, Chong Beng; He, Yicheng (Penerbit Universiti Kebangsaan Malaysia, 2023)
Liu Shao's Renwu Zhi is a classic work on the study of human talent in ancient China. Written during the tumultuous period of the end of the Eastern Han dynasty, Liu Shao recognized that the political problems of the time were rooted in issues related to human talent. Consequently, one of the primary purposes of his writing Renwu Zhi was to assist feudal dynasties in selecting and training talented individuals to address the political crisis. This paper explores Liu Shao's definition and characteristics of Caixing (talent and nature) in Renwu Zhi, which he accomplishes through the methods of Jiuzheng (nine criteria) and Baguan (eight observations), resulting in a systematic and elaborative classification of talented individuals. Moreover, the paper delves into the deeper meaning of Yingxiong (heroes). Through analysis of Liu Shao’s ideas, this paper concludes that his definitions and training methods for talented individuals have practical significance and provide valuable insights for modern talent selection and training.